Synthesis, thermal analysis, and linear and nonlinear optical characterization of substituted polyphosphonates derived from 1, 12‐dodecanediol. Issue 22 (14th September 2016) - Freeman, Jason L.; Martin, Justin R.; Totsch, T. Ross; Nia, Farid Marashi; Wang, Jianwei; Zhang, Yuanli; Yancey, Benjamin; Atkinson, Jeffrey L.; Lawson, Christopher M.; Gray, Gary M.
ABSTRACT: The syntheses of a series of substituted polyphosphonates of the type [OP(X)(Ar)O(CH2 )12 ] n (X = O, S, Se; Ar = phenyl, 2, 2′‐bithienyl‐5‐yl) are reported. The M ¯ n s for the polyphosphonates range from 1.1 to 4.6 × 10 4 Da and are significantly higher than those previously reported for polyphosphonates synthesized via polycondensation reactions. Thermal characterization indicates that all of the polymers are in the rubbery state at room temperature and have thermal stabilities as high as 290 °C. The linear absorption spectra, emission spectra, and emission quantum yields of the 2, 2′‐bithenyl‐5‐yl substituted polyphosphonates show distinct trends with respect to the chalcogen attached to the phosphorus. Solutions of these polymers show emission at wavelengths ranging from 380 to 400 nm and, depending on the choice of X, the quantum yields are considerably larger than that of 2, 2′‐bithiophene. Nonlinear optical measurements of the polyphosphonates with 2, 2′‐bithenyl‐5‐yl substituents show that nonlinear absorbance increases with increasing molecular weight of X. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3663–3674 Abstract : The syntheses of a series of polyphosphonates via the polycondensations of bis(diethylamino)(aryl)phosphines and 1, 12‐dodecandiol followed by oxidation with a chalcogen are reported. The M ¯ n s for the polyphosphonates are significantly higher than those previously reported for polyphosphonates synthesized via polycondensation reactions. Thermal characterization indicates that the polymers are in the rubbery state at room temperature, and the optical properties of the 2, 2′‐bithienyl‐5‐yl polyphosphonates have been evaluated by emission spectroscopy and nonlinear transmission measurements.